Exacerbation of Chikungunya Virus Rheumatic Immunopathology by a High Fiber Diet and Butyrate - Prow, Natalie A.; Hirata, Thiago D. C.; Tang, Bing; Larcher, Thibaut; Mukhopadhyay, Pamela; Alves, Tiago Lubiana; Le, Thuy T.; Gardner, Joy; Poo, Yee Suan; Nakayama, Eri; Lutzky, Viviana P.; Nakaya, Helder I.; et al. (Frontiers in Immunology, 2019)
Chikungunya virus (CHIKV) is a mosquito transmitted alphavirus associated with a robust systemic infection and an acute inflammatory rheumatic disease. A high fiber diet has been widely promoted for its ability to ameliorate inflammatory diseases. Fiber is fermented in the gut into short chain fatty acids such as acetate, propionate and butyrate, which enter the circulation providing systemic anti-inflammatory activities. Herein we show that mice fed a high fiber diet show a clear worsening of CHIKV arthropathy, with increased edema and neutrophil infiltrates. RNA-Seq analyses illustrated that a high fiber diet, in this setting, promoted a range of pro-neutrophil responses including Th17/IL-17. Gene Set Enrichment Analyses further demonstrated significant similarities with mouse models of inflammatory psoriasis and significant depression of macrophage resolution phase signatures in the CHIKV arthritic lesions from mice fed a high fiber diet. Supplementation of the drinking water with butyrate also increased edema after CHIKV infection. However, the mechanisms involved were different, with modulation of AP-1 and NF-κB responses identified, potentially implicating deoptimization of endothelial barrier repair. Thus neither fiber nor SCFAs provided benefits in this acute infectious disease setting, which is characterized by widespread viral cytopathic effects and a need for tissue repair.